A Comment on "Stable Spillovers among Substitutes" - Laroque, G. (Review of Economic Studies, 1981)
Journal Article A Comment on “Stable Spillovers among Substitutes” Get access G. Laroque G. Laroque Institut National de la Statistique et des Etudes Economiques Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 2, April 1981, Pages 355–361, https://doi.org/10.2307/2296892 Published: 01 April 1981 Article history Received: 01 March 1980 Accepted: 01 October 1980 Published: 01 April 1981